Key factors influencing long-term engagement: a quantitative analysis of Special Olympics World Games 2023 volunteers - Hannawacker, Antonia; Rose, Lina-Doreen; Preuss, Holger (Frontiers in Sports and Active Living, 2025)
IntroductionThe contribution of volunteers to the success of mega sport events is very valuable, as they dedicate their time and skills without financial compensation. Despite the undiminished enthusiasm for volunteering at events, grassroots sport in Europe faces increasing challenges in retaining long-term volunteers in sports clubs. This study aims to contribute to existing research by examining the characteristics and motivations of volunteers at mega sport events, with a particular focus on the Special Olympics World Games 2023 (SOWG 23). Furthermore, it seeks to identify factors that influence long-term engagement, ultimately promoting a sustainable volunteering legacy.MethodsA quantitative methodology was employed, utilizing a structured questionnaire survey conducted in the context of the SOWG 23 in Berlin. The questionnaire addressed various domains, including satisfaction, expectations, volunteering history, future volunteering intentions, perceptions of sport event characteristics, and socio-demographic variables. Additionally, an extended version of the VMS-ISE scale was employed in order to ascertain the motives of the surveyed volunteers. Following verification, 512 validated responses were subjected to analysis employing descriptive and inferential statistical methods and techniques.ResultsThe results demonstrate that most respondents were female, married or in life partnerships, without children, of advanced age, highly educated, and with prior volunteering experience despite no parental history of volunteering. Intrinsic motivations were pivotal for volunteer engagement at the SOWG 23, while extrinsic rewards had a lesser influence. The group-specific analysis, based on individual volunteering history, identified key factors that distinguished those who became active as a result of the event from those who did not. The binomial logistic regression model developed was statistically significant [χ2(18) = 48.01, p < .001] and explained a large proportion of the variance (R2 = .51).Discussion/ConclusionThis study enhances the understanding of the characteristics and motivations of volunteers engaged in the Special Olympics context, and identifies specific factors that facilitate long-term engagement. Furthermore, the findings offer invaluable insights that have informed the development of recruitment strategies aimed at fostering a volunteer legacy in both the sports and non-sports sectors.